Fatty acid composition in seeds of holoparasitic Orobanchaceae from the Caucasus region: Relation to species, climatic conditions and nutritional value - Ruraż, Karolina; Piwowarczyk, Renata; Gajdoš, Peter; Krasylenko, Yuliya; Čertík, Milan (Phytochemistry, 2020)
The specialization of parasitic plants from the Orobanchaceae family to the heterotrophic lifestyle caused several morphological, physiological and molecular changes. One of the adaptations to the parasitic lifestyle is the production of a large number of the smallest seeds in world flora, also called "dust-seeds". Seeds of 34 holoparasitic species from the Cistanche, Orobanche, Phelipanche, and Phelypaea genera were collected in the Caucasus region (54 samples) and their fatty acid content and compositions analysed. Of these seeds, 28 were investigated for the first time, and 12 are endemic to the Caucasus (one of the most important biodiversity hotspots in the world). The influence of different hosts, populations, habitats, and climatic conditions on the fatty acid content and composition, as well as some connections of taxonomic classification are discussed. The fatty acid content in the species varied between 0.9 and 42.5%, and showed quantitative differences at generic and infrageneric levels, while displaying uniform fatty acid composition. Thirteen fatty acids were identified, of which nine were undescribed for Orobanchaceae. The fatty acid composition of the Orobanchaceae seeds represented a mixture of saturated fatty acids (SFAs) (average 7.8%) and unsaturated fatty acids (UFAs) (average 92.2%). The fatty acid content in the Orobanchaceae seeds was directly unrelated to taxonomy, while the n-6/n-3 fatty acid ratio supported the clear separation of the Orobanche and Phelipanche genera. Orobanchaceae seeds contained mainly linoleic and oleic acids, thus they could be a potential nutritional source of the unsaturated fatty acids. Additionally, the studies confirmed the hypothesis that the degree of seed oil fatty acid unsaturation increased in colder climatic conditions, especially for the Orobanche genus.
Keywords: oleje rostlin; Fatty acid composition; Orobanchaceae; Chemotaxonomy; Nutritional properties; nutriční hodnota; mastné kyseliny; Host; Plant Oils; Climatic conditions; Orobanche; Nutritive Value; Orobancheae; Seeds; Fatty Acids; Dust seeds; semena rostlinná